A Randomized Comparison Between Interscalene and Small-Volume Supraclavicular Blocks for Arthroscopic Shoulder Surgery. Issue 6 (August 2018) - Aliste, Julián; Bravo, Daniela; Fernández, Diego; Layera, Sebastián; Finlayson, Roderick J.; Tran, De Q.
Abstract : Background and Objectives: This randomized trial compared ultrasound (US)–guided interscalene block (ISB) and small-volume supraclavicular block (SCB) for arthroscopic shoulder surgery. We hypothesized that SCB would provide equivalent analgesia to ISB 30 minutes after surgery without the risk of hemidiaphragmatic paralysis (HDP). Methods: All patients received an US-guided intermediate cervical plexus block. In the ISB group, US-guided ISB was performed with 20 mL of levobupivacaine 0.5% and epinephrine 5 μg/mL. In the SCB group, US-guided SCB was carried out using 20 mL of the same local anesthetic agent: 3 and 17 mL were deposited at the "corner pocket" (ie, intersection of the first rib and subclavian artery) and posterolateral to the brachial plexus, respectively. A blinded investigator assessed ISBs and SCBs every 5 minutes until 30 minutes using a composite scale that encompassed the sensory function of the supraclavicular nerves, the sensorimotor function of the axillary nerve, and the motor function of the suprascapular nerve. We considered the blocks complete if, at 30 minutes, a composite score equal or superior to 6 points (out of 8 points) was achieved. Thus, onset time was defined as the time required to reach a minimal composite score of 6 points. The blinded investigator also assessed the presence of HDP at 30 minutes with US. Subsequently, all patients underwent general anesthesia. Postoperatively, a blinded investigator recorded pain scores at rest at 0.5, 1, 2, 3, 6, 12, and 24 hours. Patient satisfaction at 24 hours, consumption of intraoperative and postoperative narcotics, and opioid-related adverse effects were also tabulated. Results: Both groups displayed equivalent postoperative pain scores at 0.5, 1, 2, 3, 6, 12, and 24 hours. Interscalene blocks resulted in a higher incidence of HDP (95% vs 9%; P < 0.001), a shorter onset time, and a higher proportion of patients with minimal composite scores of 6 points at 30 minutes (100% vs 77%; P = 0.048). However, no intergroup differences were found in terms of performance time, procedural pain, number of needle passes, intraoperative/postoperative opioid consumption, adverse effects, and patient satisfaction at 24 hours. Conclusions: Compared with ISB, small-volume SCB results in equivalent postoperative analgesia and a lower incidence of HDP. Because the latter cannot be completely avoided with small-volume SCB, further trials are required to investigate the optimal diaphragm-sparing nerve block for shoulder surgery. Clinical Trial Registration: This study was registered at ClinicalTrials.gov, identifier NCT03224884.